Autosomal dominant cerebellar ataxia with retinal degeneration (ADCA II): clinical and neuropathological findings in two pedigrees and genetic linkage to 3p12-p21.1. Issue 4 (April 1997) - Jöbsis, G J; Weber, J W; Barth, P G; Keizers, H; Baas, F; van Schooneveld, M J; van Hilten, J J; Troost, D; Geesink, H H; Bolhuis, P A
Abstract : OBJECTIVES: To investigate relations between clinical and neuropathological features and age of onset, presence of anticipation, and genetic linkage in autosomal dominant cerebellar ataxia type II (ADCA II). METHODS: The natural history of ADCA II was studied on the basis of clinical and neuropathological findings in two pedigrees and genetic linkage studies were carried out with polymorphic DNA markers in the largest, four generation, pedigree. RESULTS: Ataxia was constant in all age groups. Retinal degeneration with early extinction of the electroretinogram constituted an important component in juvenile and early adult (< 25 years) onset but was variable in late adult presentation. Neuromuscular involvement due to spinal anterior horn disease was an important contributing factor to illness in juvenile cases. Postmortem findings in four patients confirm the general neurodegenerative nature of the disease, which includes prominent spinal anterior horn involvement and widespread involvement of grey and white matter. Genetic linkage was found with markers to chromosome 3p12-p21.1 (maximum pairwise lod score 4.42 at D3S1285). CONCLUSIONS: The sequence of clinical involvement seems related to age at onset. Retinal degeneration is variable in late onset patients and neuromuscular features are important in patients with early onset. Strong anticipation was found in subsequent generations. Linkage of ADCA II to chromosome 3p12-p21.1 is confirmed.